2019
DOI: 10.1021/jacs.8b10990
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR and MD Study of the Structure of the Statherin Mutant SNa15 on Mineral Surfaces

Abstract: Elucidation of the structure and interactions of proteins at native mineral interfaces is key to understanding how biological systems regulate the formation of hard tissue structures. In addition, understanding how these same proteins interact with non-native mineral surfaces has important implications for the design of medical and dental implants, chromatographic supports, diagnostic tools, and a host of other applications. Here, we combine solid-state NMR spectroscopy, isotherm measurements, and molecular dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 109 publications
0
22
0
Order By: Relevance
“…In a similar biological context, metadynamic metainference and NMR chemical shifts were exploited by Hultqvist et al to get insights into the interaction of the two disordered proteins CID and NCBD [143]. Backbone chemical shifts were also used by Buckle et al to investigate the interaction of the SNa15 peptide with non-native mineral surfaces [144]. Finally, concerning NMR, RDC data were employed in the metainference framework by Weber and coworkers to study the conformational space accessible to the LC protein [145].…”
Section: Enforcing Experimental Information During the Simulationsmentioning
confidence: 99%
“…In a similar biological context, metadynamic metainference and NMR chemical shifts were exploited by Hultqvist et al to get insights into the interaction of the two disordered proteins CID and NCBD [143]. Backbone chemical shifts were also used by Buckle et al to investigate the interaction of the SNa15 peptide with non-native mineral surfaces [144]. Finally, concerning NMR, RDC data were employed in the metainference framework by Weber and coworkers to study the conformational space accessible to the LC protein [145].…”
Section: Enforcing Experimental Information During the Simulationsmentioning
confidence: 99%
“…The CaP-SLiMs in Table 1 do not appear to contain or flank any of the recognized motifs associated with binding phosphate anions such as anion nests or P-loops containing a basic residue (GXXXXGK(S,T)) [51][52][53]. The involvement of basic residues in the folding and binding of the N-terminal region of statherin to HA has been reported [54][55][56]. However, much more work is needed to investigate the potential co-binding to calcium and P i ions in the CaP by basic and acidic residues in or around the CaP-SLiM sequences.…”
Section: Calcium Phosphate-binding Short Linear Motifs (Cap-slims)mentioning
confidence: 99%
“…The dentin matrix phosphoprotein 1 (DMP1) provides an example of the The interaction between the charged residues of IDPs and mineralized surfaces can, in some instances, induce or stabilize specific secondary structures. For example, the N-terminal region of statherin adopts an α-helical conformation upon absorption to mineral surfaces [54,55]. It has been suggested that this folding upon binding prevents further growth of HA by shielding the surface of the mineral phase from further addition of CaP [54].…”
Section: Conformational Flexibility and Adaptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…1 Therefore, when considering the use of a particular additive to control crystal growth or morphology, it is important to investigate the thermodynamically stable conformations of the additives at various crystal surfaces. Although certain experimental techniques, such as infrared spectroscopy 2 and solid-state NMR, 3 can reveal information about the conformations of additives at wide crystal surfaces, the detailed conformations and dynamics of additives at specific planes of crystals grown in solution are difficult to determine experimentally.…”
Section: Introductionmentioning
confidence: 99%